The Relationship Between Adaptive Leadership and Organizational Support and Teachers’ Ability in Elementary School Curriculum Changes - Nanda Darmawan; Usman Radiana; Eni Rosnija; Husni Syahrudin; Henny Sanulita (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This study investigates the relationship between adaptive leadership and organizational support and teachers’ ability to cope with curriculum changes at SDN 28 Pontianak Kota. Using a quantitative explanatory design, all 20 teachers were selected through saturated sampling. Data were collected with a Likert-scale questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) via SmartPLS by evaluating the measurement and structural models. The findings show that adaptive leadership has a positive but non-significant relationship with teachers’ ability to cope with curriculum changes (β = 0.312; t = 0.810; p = 0.419). Organizational support also shows a positive but non-significant relationship, with a stronger coefficient (β = 0.444; t = 1.156; p = 0.248). Together, both variables explain 51.8% of the variance in teachers’ ability (R² = 0.518). These results suggest that teachers’ readiness for curriculum change is shaped not only by individual factors but also by school leadership and organizational support. The study underscores the need for sustained support.